Membangun Karakter dengan Olahraga (Jalan Sehat) dalam Memperingati HUT RI di Dukuh Gatak Gede - Muhammad Fajrul Falaah; Muhammad Jalari (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
This community service has the main purpose of building community character through sports activities in commemoration of the Anniversary of the Republic of Indonesia (HUT RI) in Gatak Gede Hamlet. The commemoration of the Indonesian Independence Day is not just an annual ceremony, but a momentum to foster a sense of love for the homeland and strengthen social ties between citizens. The background of this activity is based on the importance of instilling character values such as sportsmanship, togetherness, discipline, and the spirit of nationalism. These values are believed to be developed effectively through enjoyable physical activities, involving all levels of society, and having a positive impact on social life. The method of implementing the activity was carried out in a healthy way which was followed by participants from various circles, ranging from children, adolescents, to adults who live in Gatak Gede Hamlet, Kateguhan, Sawit, Boyolali. Healthy walking was chosen because it is a simple sports activity that is easy to do, can reach a wide range of ages, and has great benefits both physically and socially. In addition, healthy walks are a means of joint recreation that can give rise to positive interactions between residents, thereby fostering a sense of togetherness. The goals to be achieved through this activity are to strengthen social relations, strengthen the spirit of mutual cooperation, and instill the value of togetherness in the community. Healthy walks carried out in the framework of the Indonesian Independence Day have proven to be an effective means to build positive character, foster a sense of unity, and improve physical health.